THE SOCIAL EFFICIENCY OF CONSUMPTION: PROBLEMS AND EVALUATION - Igor K. Beliaevskiy (Статистика и экономика)
The problem of study and estimation ofsocial efﬁciency of consumption, namely, the results of satisfaction of needs throughboth the mediation of market and non-market channels is considered in this article. The concept and content of these phenomena and processes are unveiled,the speciﬁc features of formation of their results and effectiveness are revealed. The materials of state statistics treated by the author were used for the purposesof this study.